Toward three-dimensional modeling of the interaction between the air flow and a clamped–free yarn inside the main nozzle of an air jet loom. Issue 6 (March 2019) - Osman, Akil; Delcour, Lucas; Hertens, Ine; Vierendeels, Jan; Degroote, Joris
In air jet looms, the weft yarn is transported from the prewinder to the reed by means of an air flow. In this work, the motion of a yarn inside a main nozzle during the first stage of an insertion process is modeled and analyzed. In this stage, the weft yarn is clamped at one side and free at the other side. Therefore, the deformation waves of a clamped–free yarn are modeled. A three-dimensional, two-way, fluid–structure interaction simulation has been performed in which the yarn is represented as a flexible cylinder and the arbitrary Lagrangian–Eulerian technique is employed. The results of the simulation have been compared quantitatively and qualitatively with experiments. It was, however, not possible to match the initial position and stress state of the yarn in the simulations to that in the experiments. This causes large differences between the simulated and measured yarn positions and wave characteristics, especially at the beginning. The agreement between experimental and simulated wave characteristics notably improves as time progresses, but substantial differences remain. Analyzing the overall motion of the yarn inside the main nozzle shows that the mixing region, where the shocks are located, can be considered as an excitation point. In this point, the aerodynamic normal forces are high if the yarn is not located on the axis of the main nozzle. All deformation waves start from the mixing region and propagate along the yarn.